Perencanaan paket dan jalur trekking agrowisata petualangan Rawa Gede coffee tour di desa Sirnajaya, Sukamakmur, Bogor, Jawa Barat - Revi Agustin Aisyianita; Maesa Quratuain; Amelia Dwi Juliana; Siti Hanatul Puadah; Zahira Khoirunnisa; Yuniatika; Dwi Indah Nurhaliza; Dio Harianto Putra; Farchan Sholla Nurhafiz; Akhady Imam Pratomo; Akmal Adil (STIE Pariwisata API Yogyakarta, 2023)
This study aims to (1) identify attractions, amenities, accessibilities, and ancillary agro-adventure tourism in the Rawa Gede areas; (2) design the Rawa Gede Coffee Tour adventure agro-tourism package; (3) design trekking routes for the Rawa Gede Coffee Tour adventure agrotourism package. Based on the results of the Focus Group Discussion (FGD) with the coffee farmer group and the POKDARWIS of Sirnajaya Village and the results of field observations and simulations of trekking routes by researchers, one - day tour package and one trekking route with a distance of about 6.6 km and a travel time of 3-4 hours.